The impact of family members on aging persons’ technology use intentions - Freek Van Baelen; Melissa De Regge; Bart Larivière; Katrien Verleye; Kristof Eeckloo (Heliyon)
Technology plays a growing role in allowing aging persons to live independently. However, it is often difficult to motivate aging persons to use these new technologies. Using 182 dyads of aging persons and their primary family caregiver, this study investigates how family members' beliefs about the capabilities of the aging person are associated with the aging person's engagement in using healthcare technology—a phenomenon known as the Pygmalion effect. A quantitative statistical method response-surface analysis (RSA) was performed. RSA is often employed to understand complex, nonlinear interactions within a data set. It was investigated how the level of fit (when both the aging person and his or her family caregiver hold similar beliefs about the technological capabilities of the aging person) and the direction of misfit (whether the abilities of the aging person are greater or worse than the family caregiver thinks) shape the aging person's intention to use healthcare technologies. The individual perception of capabilities is an important driver of the intention to use technology. In line with the Pygmalion effect, the effects of family members on aging persons drives their adoption of healthcare technology. The greatest intentions to use technology are observed when there is a fit in beliefs. In contrast, misfit leads to lower usage intentions. The direction of misfit further reveals that aging person's beliefs about their capabilities are more decisive than their family caregiver's beliefs in promoting their technology usage intentions. In addition, age, experience with technology, attitudes, social norms, and technological savviness in the family also have an impact on aging persons' intentions to use technology. This study extends the theoretical basis of the Pygmalion effect by including fit, misfit, and direction of (mis)fit.